African Charter on Democracy, Elections and Governance (ACDEG) and Leadership Recruitment in Nigeria: An Appraisal of People’s Democratic Party (PDP), 2010 – 2020 - Ifedi , Francisca Obiageli; Uzogbado , Donatus Okechukwu (University of Nigeria Journal of Political Economy, 2021)
A well-developed internal party democracy is one of the factors that make for credible elections. African Charter on Democracy, Elections and Governance (ACDEG), an arm of the African Union is determined to promote and strengthen good governance through the institutionalization of transparency, accountability and participatory democracy throughout Africa. This paper examined the impact of ACDEG on leadership recruitment in Nigeria using the People’s Democratic Party (PDP) as its focus of analysis. It aimed to investigate: how the inability to implement the ACDEG guidelines affected internal party democracy of PDP; the relationship between incumbent factors and impositions of candidates of PDP; and the extent to which Nigeria’s electoral institutions complied with the ACDEG’s guidelines on monitoring of party activities during the period 2010-2020. The study adopted the elite theory as its framework of analysis and the ex-post-facto research design. It found that the inability of PDP to abide by ACDEG’s guidelines undermined its internal democracy; that there was relationship between incumbent factor and imposition of candidates in PDP; and that Nigeria’s electoral institutions did not comply substantially with the ACDEG’s guidelines on monitoring of party activities between 2010 and 2020. We recommended, among other things, the overhauling of Nigeria’s electoral laws to bring them in conformity with the ACDEG guidelines.